Pengembangan Perangkat Pembelajaran Model Discovery Learning Materi Gerak Lokomotor Kelas Rendah Sekolah Dasar - Hamzah, Hamzah; Mu’arifin, Mu’arifin; Heynoek, Febrita Paulina; Kurniawan, Rama; Kurniawan, Ari Wibowo (Universitas Negeri Malang, 2020)
In advancing the national education system, the government has innovated in developing a learning model that is in accordance with the 2013 curriculum guidelines, but in reality the idea has not been implemented evenly, including elementary schools in Pasuruan district from the results of the researcher's preliminary study. Researchers developed learning tools in the form of a learning implementation plan, teaching materials and evaluation monitoring (Monev) guidelines based on the Discovery Learning model. In carrying out research and development researchers used the Borg and Gall (1989) method. The results of product development in small trials (81%) and large trials (84%). The conclusion of this product development is valid and can be implemented in learning.Dalam memajukan sistem pendidikan nasional pemerintah berinovasi dalam mengembangkan model pembelajaran yang sesuai dengan pedoman kurikulum 2013, tetapi pada kenyataannya gagasan tersebut belum terlaksana secara merata termasuk sekolah dasar (SD) di kabupaten Pasuruan dari hasil studi pendahuluan peneliti. Peneliti mengembangkan perangkat pembelajaran berupa rencana pelaksanaan pembelajaran (RPP), bahan ajar dan panduan monitoring evaluasi (Monev) berbasis model Discovery Learning. Dalam melaksanakan penelitian pengembangan peneliti menggunakan metode Borg and Gall (1989). Hasil pengembangan produk pada uji coba kecil (81%) dan uji coba besar (84%). Kesimpulan pada pengembangan produk ini adalah valid dan dapat diimplementasikan dalam pembelajaran.